Environmentally persistent free radicals from residential raw coal combustion and association with chemical components - Kai Xiao; Li Li; Yongqiang Zhang; Yousong Zhou; Donglei Fu; Zhihan Luo; Tianyao Huang; Senlin Lu; Fenwu Liu; Jiakuan Lu; Qingyue Wang; Guofeng Shen (Emerging Contaminants)
Emerging environmental persistent free radicals (EPFRs), can generate reactive oxygen species (ROS), posing potential exposure risks to human health. Incomplete coal combustion is a major source of EPFRs. Organic carbonaceous fractions are essential and important players in the formation of EPFRs during coal combustion. However, relationship between individual organic carbonaceous and non-carbon fractions with EPFRs in such emissions are not well known. This paper investigated the characteristics of EPFRs discharged from simulated coal combustion. Our results showed that the concentration of EPFRs was major concentrated on PM1.1 (51.66–81.85 %), and more easily oxidized by oxygen resulting in producing more oxygen-centered radicals (semiquinone-type) in PM1.1. The mean of line width (ΔHp-p) was 5.87 ± 0.41G higher than that of biomass combustion, indicating more free radical species were emitted from coal combustion. Humic-like substances-carbon (HULIS-C) was the major contributor of the formation of EPFRs and facilitate the generated of EPFRs. Secondary processes have also contributed to the formation of EPFRs during the coal combustion. Our result also noted that there was no relationship between transition metals and EPFRs, may be due to the variability and complexity of the chemical properties and composition of PM. This is critical for the prediction of geochemical behavior and risk assessment of EPFRs, which can provide basic data to support policy development to address rural air pollutant emissions.